2020
DOI: 10.30564/jzr.v2i2.2054
|View full text |Cite
|
Sign up to set email alerts
|

Review on use of macro algae (seaweed) in fish nutrition

Abstract: Currently, the search is on for alternative sources of feed ingredients, the main reasons being escalated cost and uncertainty of constant supply of common feed ingredients. The importance of algae as a potential substitute protein source for cultured fish feeding has been documented in recent years. Seaweeds are receiving consideration for their high protein value, essential amino acid content, vitamins and trace metals in fish feeding. As well as marine macro algae could be a potential low-cost source of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…6-19.4%, ash 22.2-48.9%, lipid 0.8-7.2%, carbohydrates 11.8-64.0% and moisture 74.7-94.3% (de Gaillande et al, 2017). In addition, macroalgae also have other important nutrients such as amino acids, fatty acids, beneficial polysaccharides, antioxidants, vitamins and minerals (Ismail et al, 2017;Saleh, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6-19.4%, ash 22.2-48.9%, lipid 0.8-7.2%, carbohydrates 11.8-64.0% and moisture 74.7-94.3% (de Gaillande et al, 2017). In addition, macroalgae also have other important nutrients such as amino acids, fatty acids, beneficial polysaccharides, antioxidants, vitamins and minerals (Ismail et al, 2017;Saleh, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…There are many studies on macroalgae as an alternative source of protein. In the world's marine waters, more than 400 macroalgae have been found that contain abundant protein, amino acids and minerals (Saleh, 2020), so they have the potential to be used to increase fish growth. The use of the macroalga Ulva lactuca as a feed additive for growth has been given to African catfish, Clarias gariepinus and Nile tilapia, Oreochromis niloticus L. (Abdel-Warith et al, 2016;Natify et al, 2015), Ulva fasciata and Enteromorpha flaxusa applications on the growth of rabbitfish, Siganus rivulatus fry (Abdel Aziz & Ragab, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing these figures with, for example, the production of terrestrial cereals, which is about 3 billion tonnes (https://www.fao.org/faost at/ en/#data/QCL; https://ourwo rldin data.org/agric ultur alprodu ction), shows that presently seaweeds produce only a minor fraction of the global supply of biomass used by humans (Buschmann et al, 2017). Although off-shore cultivated seaweeds could potentially provide a sustainable alternative source of biomass for food and feed, that can release the pressure on arable land and fresh water resources, several basic questions have to answered (Buschmann et al, 2017); first of all, the question on the nutritional value, digestibility, and bio-availability of seaweed compounds for humans, livestock, poultry, and fish (Buschmann et al, 2017;Saleh, 2020;Wells et al, 2017). Wells et al (2017) emphasized that collaborative approaches between among others phycologists and nutritional and medical groups are required to study how algal nutritional and functional constituents interact in human metabolism.…”
Section: Seaweedmentioning
confidence: 99%
“…In some cases, the growth, nutrient utilization, and other information such as enzyme activity and hematological parameters have been compared for fish (Huda et al, 2020;Kim et al, 2021;Lawal et al, 2017;Pongpet et al, 2016;Tippayadara et al, 2021;Wang et al, 2018;Zheng et al, 2012) and shellfish (Moniruzzaman et al, 2020). Aside from fishmeal, several alternative feed ingredients, such as those of animal protein origin, insects, land animal byproducts, fisheries by-products, worms, and plant-based protein sources, including algae such as Chlorella and spirulina, have been evaluated as feed ingredients in both fresh and marine water fish production (Ansari et al, 2021;Raji et al, 2018Raji et al, , 2019Saleh, 2020).…”
Section: Introductionmentioning
confidence: 99%